Motion control of nonholonomic robots at low speed. (20th February 2020) - Miková, Ľubica; Gmiterko, Alexander; Kelemen, Michal; Virgala, Ivan; Prada, Erik; Hroncová, Darina; Varga, Martin
Many applications in robotics require precise tracking of the prescribed path. The aim of this article is to develop and verify by computer simulation a control design method which ensures that the "output" of the robot will move along a prescribed path. A virtual vehicle approach algorithm was used to track a predefined vehicle path. The idea behind this algorithm is that the movement of a virtual vehicle on a predefined path is controlled by a differential equation whose input is a control deviation representing the distance between a real and a virtual vehicle. The main advantage of the path-following approach is that, based on this approach, the feedback realized is invariant to the path.